Inhibition of Wnt-β-Catenin Signaling by ICRT14 Drug Depends of Post-Transcriptional Regulation by HOTAIR in Human Cervical Cancer HeLa Cells - Trujano-Camacho, Samuel; Cantú-de León, David; Delgado-Waldo, Izamary; Coronel-Hernández, Jossimar; Millan-Catalan, Oliver; Hernández-Sotelo, Daniel; López-Camarillo, César; Pérez-Plasencia, Carlos; Campos-Parra, Alma D. (Frontiers in Oncology, 2021)
Background. In Cervical cancer (CC), in addition to HPV infection, the most relevant alteration during CC initiation and progression is the aberrant activation of Wnt/β-catenin pathway. Several inhibitory drugs of this pathway are undergoing preclinical and clinical studies. Long non-coding RNAs (lncRNAs) are associated with resistance to treatments. In this regard, understanding the efficiency of drugs that block the Wnt/β-catenin pathway in CC is of relevance to eventually propose successful target therapies in patients with this disease. Methods: We analyzed the levels of expression of 249 components of the Wnt/β-catenin pathway in a group of 109 CC patients. Three drugs that blocking specific elements of Wnt/β-catenin pathway (C59, NSC668036 and ICRT14) by TOP FLASH assays and qRT-PCR were tested in vitro in CC cells. Results: 137 genes of the Wnt/β-catenin pathway were up-regulated and 112 down-regulated in CC patient’s samples, demonstrating that this pathway is dysregulated. C59 was an efficient drug to inhibit Wnt/β-catenin pathway in CC cells. NSC668036, was not able to inhibit the transcriptional activity of the Wnt/β-catenin pathway. Strikingly, ICRT14 was neither able to inhibit this pathway in HeLa cells, due to HOTAIR interaction with β-catenin, maintaining the Wnt/β-catenin pathway activated. Conclusions: These results demonstrate a mechanism by which HOTAIR evades the effect of ICRT14, a Wnt/β-catenin pathway inhibitory drug, in HeLa cell line. The emergence of these mechanisms reveals new scenarios in the design of target therapies used in cancer.